Kith and kin affinities and inter-state engagements: an analysis of the international community’s reactions to Zimbabwe’s fast-track land reform programme - Muzvidziwa, Joe (Midlands State University, 2021)
This thesis on ‘Kith and Kin Affinities and Inter-State Engagements: An analysis of the International Community’s Reactions to the Zimbabwe’s Fast-Track Land Reform’ (FTLR) programme probes the international community’s intersecting, conflicting and racialised responses to Zimbabwe’s post-2000 radical land reform process. Most countries in the Southern African Development Community (SADC) sub-region and their respective leadership who viewed the late President Robert Mugabe as a committed revolutionary and exemplary Pan-Africanist considered the FTLR programme as a decolonial exercise, a case of Blacks justifiably retaking their patrimony. This view resonated with the anti-colonial sentiments prevalent in the SADC sub-region, especially in the countries led by former armed liberation movements such as Angola, Mozambique, Namibia and South Africa. The ruling parties of these countries revived their erstwhile armed liberation struggle’s solidarity networks to guard against what they perceived as imperial snooping in Zimbabwe’s internal affairs. Western countries on the contrary, applied the neo-imperial governance debate by opposing the FTLR programme for violating property and human rights. Essentially, the West punished Zimbabwe through economic sanctions and ostracisation on the international arena for retaking its land from approximately 4 500 White farmers, representing 5% of the population, but owned 80% of the prime land in the country. The contradictory positions between the African and Western countries reveal the racial fault-lines in the international community’s reactions to Zimbabwe’s FTLR programme. Therefore, it is revealed in this study that kith and kin ideas informed the opposing African and western communities’ orientations towards Zimbabwe’s IndigenousBlacks’ repossession of the country’s prime land from the minority White farmers. The study further observed that kith and kin affinities and inter-state engagements failed to address the land imbalances in Zimbabwe and protected the land invasions when the process was internationalised through the SADC Tribunal. China and Russia remained neutral in their engagements with Zimbabwe, largely because of ideological reasons. Both countries pursued an international relations policy premised on the ideal of noninterference in the domestic affairs of other countries. The development of effective communications at all levels in national survival programmes will address the polarisation challenge that has left Zimbabwe exposed to negative external influence in its debates on national survival issues. This thesis was grounded on the Social Constructivism Theory which used the qualitative research methodology and deployed the interpretive and critical philosophy. The narrative design, utilised the thematic and content technique for data analysis.